CHRISTOLOGY: UNDERSTANDING FAITH AND CHALLENGES OF THE CONTEMPORARY WORLD - Marques Alves, Viviane; de Fraga Gomes, Tiago (Revista Gênero e Interdisciplinaridade, 2026)
The work and person of Jesus Christ are studied through Christology, which provide knowledge about his humanity and divinity. In his humanity, Jesus Christ approaches human beings in form, yet perfectiy and without sin. On the other hard, in his divinity he makes it clear that he is god. Social cristology adresses faith within Society, in human and social relationships. Human dignity, a fundamental principle for a the protection of human rights, was already presente in Jesus actions, as he cared for the poor, oppressed, children, and thev elderly Where his love for humanity proves this. This dignity i salso highlighted When facing religious intolerance and prejudice, something unacceptable in todays world.